Fatigue behaviour of fiber reinforced polymers experiments and simulations : Fifth International Conference on Fatigue of Composites (ICFC5) Nanjing University of Aeronautics and Astronautics in Nanjing (NUAA), China, October 16-19, 2010 - Yao, Weixing; Renard, Jacques; Himmel, Norbert A. (DEStech Publications, 2012)
Book is organized around new experiments in and modeling of fatigue and its effects over a range of composite materials subjected to multiple mechanical and thermal stresses. An objective of the investigations discussed is to explain failure mechanisms and improve long-term loading prediction and performance. Chapters in the book are edited and refereed presentations made at the most recent ICFC5 conference, held in Nanjing, China.